6x+6y=36
2x-6y=-60
adding both the equations
6x+6y=36
2x-6y=-60
---------------
8x =-24
x=-3
substituting in1 equation
6*-3+6y=36
-18+6y=36
6y=36+18
6y=54
y=9
therefore the solution is (-3,9)
if you think sometimes your answer is wrong just verify your answer by substituting the x and y values in the first or the second equation.
6*-3+6*9=36
-18+54=36
36=36
therefore LHS =RHS
2007-05-16 23:02:40
·
answer #1
·
answered by neha 1
·
0⤊
0⤋
Add both equations together. You'll see that the "6y" terms cancel out. In fact, you're left with:
8x = -24
x = -3
Then, take either equation (doesn't matter which) and plug x = -3 in and solve for y:
6(-3) + 6y = 36
-18 + 6y = 36
6y = 54
y = 9
The solution is (x,y) = (-3, 9).
Plug these numbers back into both equations to ensure that you have the right answer.
6(-3) + 6(9) = -18 + 54 = 36
2(-3) - 6(9) = -6 - 54 = -60
2007-05-16 22:45:42
·
answer #2
·
answered by Eddie K 4
·
0⤊
0⤋
Since the y terms are opposites, the first step is easy. Just add the two equations together:
(6x + 6y) + (2x - 6y) = 36 + (-60)
8x = -24
x = -3
==========
Now go back to the original equations. We want to add the two x terms together to get them to cancel out. In order to do that, we need to multiply the second equation by (-3).
(-3)(2x - 6y = -60)
becomes
-6x + 18y = 180
Now, add the two equations together.
(6x + 6y) + (-6x + 18y) = 36 + 180
24y = 216
y = 9
==================
So the solution is (-3, 9)
=========
NOTE: Once you found x = -3, you can use substitution to find y. I used elimination both times to show you how to do elimination.
2007-05-16 22:46:06
·
answer #3
·
answered by Mathematica 7
·
0⤊
0⤋
6x + 6y= 36 let call 1
2x - 6y= -60 let call 2
8x = -24
x = -3
sub x = -3 into 1
6x + 6y= 36
6( -3)+ 6y= 36
-18 + 6y= 36
6y= 36 + 18
6y= 54
y=9
The answer is
x= -3
y=9
2007-05-16 22:56:40
·
answer #4
·
answered by need_need 1
·
0⤊
1⤋
Adding gives:-
8x = - 24
x = - 3
-18 + 6y = 36
6y = 54
y = 9
x = - 3 , y = 9
2007-05-16 22:47:14
·
answer #5
·
answered by Como 7
·
0⤊
0⤋
function1: 6x + 6y= 36
function2: 2x - 6y= -60
f1+f2:
8x=-24
x=-3
plug back into any of the 2 eqns
2(-3) - 6y = 60
-6-6y=60
-6(1+y)=60
1+y=-10
y=-11
answer: (-3,-11)
2007-05-16 22:44:35
·
answer #6
·
answered by electric 3
·
0⤊
0⤋
8x+7y=32 __(1) -6x+3y=-24 ___(2) [multiply (1) by 3 and (2) by 4] 24x + 21y = 96 __(3) -24x + 12y = -96 __(4) [add (3) and (4)] 33y = 0 y = 0 [from (1)] 8x + 7(0) = 32 8x = 32 x = 32/8 x = 4 so (x,y) = (4,0) ANS. (a)
2016-05-20 18:11:07
·
answer #7
·
answered by ? 4
·
0⤊
0⤋
after elim;
6x+2x=36-60
8x=-24
x= -24/8
x= -3
2007-05-16 22:50:40
·
answer #8
·
answered by gracegptx 2
·
0⤊
0⤋
Add both.
8x = -24
x = -3
y = 9
2007-05-16 22:58:03
·
answer #9
·
answered by nayanmange 4
·
0⤊
0⤋